Perbandingan Analisis Pengendalian Persediaan Barang Consumable Menggunakan Metode Min-Max dan EOQ Pada Supplier General Trading UD. Hasta Jaya - Tuffachatul Achla; Efta Dhartikasari Priyana; Yanuar Pandu Negoro (Universitas Islam Raden Rahmat, Malang, 2024)
UD. Hasta Jaya is a company engaged in supplier general trading, supplying various types of consumable goods including cloth and plastic rubber elbows. The company's lack of attention to inventory control flow is a major problem so that it can result in losses that will be experienced by the Company financially and operationally. To calculate the efficiency of inventory management, namely by knowing the components, the optimal order quantity in one order, and knowing the total inventory cost in reducing costs using 2 Min-Max and EOQ inventory control methods. The results of the calculation with the EOQ method were ordered 7 times, the order quantity was 949 Kg and 842 Kg at a cost of Rp 930,141 and Rp 929,704. As for the Min-Max method, namely 26 orders, with quantities of 241 Kg and 122 Kg and costs of Rp 1,948,873 and Rp 3,270,342.